Aplicação da densidade de kernel para atendimento do SAMU na cidade de Mossoró - Almeida Filho, Ivo Alvarenga de (Universidade Federal Rural do Semi-Árido, 2020)
Accidents and sudden ills are likely to happen to anyone. In these cases, the mobile emergency care service is necessary when the patient does not have the ability to move to a physical emergency care unit. Therefore, to maximize a patient's chances of survival, it is necessary to serve him as quickly and efficiently as possible. With this information, it is possible to generate systems that can optimize the entire process in order to reduce the waiting time for patients and even save lives, being a public health issue. So, this work makes an analysis of the areas that occur more calls, using Kernel density (heat map), from an analysis made in a period of four months within the urban area of the city of Mossoró / RN. From this, it was possible to identify places that have a higher frequency of calls. With the data obtained, it was possible to demarcate areas for the care of each ambulance and discover the time of greatest demand.
Keywords: SAMU; Mapa de calor; Densidade Kernel; Saúde pública; SAMU; Heat map; Kernel Density; Public health; ENGENHARIAS::ENGENHARIA DE PRODUCAO